Ultra-wideband slot-loaded planar antenna for future 5G millimeter wave applications - Gupta Surendra Kumar R. (Savez inženjera i tehničara Srbije, 2021)
An ultra-wideband, compact planar antenna with defected ground structure (DGS) has been presented in this article for future 5G millimeter-wave applications. The proposed antenna overcomes the limitation of bandwidth of the conventional microstrip patch antenna (typically < 5%). The antenna exhibits an ultra-wideband characteristic covering frequency band from 21.3 GHz to 40.6 GHz which makes the fractional bandwidth of 62.36%. The antenna performance is enhanced by etching slots on the patch and incorporating defect on the ground plane. The antenna achieves gain greater than 4.01 dBi and radiation efficiency greater than 95% throughout the operating band. In the given band it also exhibits very low cross-polarization level as well as stable radiation performance. This antenna is designed to operate in n257, n258, n260 and n261 5G millimeter-wave spectrum.